Risk Analysis in Software Cost Estimation: A Simulation-Based Approach - Ruchi Mittal, Vikram Singh, Varun Malik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Risk analysis and cost estimation are two important aspects of project planning that can either make the way or break the way to a project’s success. At the same, both these tasks are difficult and painstaking, but whether someone likes it and not, the project’s success depends heavily on them. As documented by Fredric Brooks Junior in his legendry book “The Mythical Man-Month,” planning, scheduling, and estimation have been central to software engineering since its early days in the 1970s. Present communication presents a simulation-based approach to estimate the costing schedule of a software development project. The results show that simulation is expedient as well as efficient in terms of time, effort, and cost requirement and provides pragmatic results.